2008
DOI: 10.1128/mcb.00880-07
|View full text |Cite
|
Sign up to set email alerts
|

The Xeroderma Pigmentosum Group E Gene Product DDB2 Activates Nucleotide Excision Repair by Regulating the Level of p21Waf1/Cip1

Abstract: The xeroderma pigmentosum group E gene product DDB2, a protein involved in nucleotide excision repair (NER), associates with the E3 ubiquitin ligase complex Cul4A-DDB1. But the precise role of these interactions in the NER activity of DDB2 is unclear. Several models, including DDB2-mediated ubiquitination of histones in UV-irradiated cells, have been proposed. But those models lack clear genetic evidence. Here we show that DDB2 participates in NER by regulating the cellular levels of p21 Waf1/Cip1 . We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
65
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 57 publications
4
65
1
1
Order By: Relevance
“…These results are consistent with the finding that an ATR-dependent pathway is essential for triggering the down-regulation of p21 after UV irradiation in mammalian cells (Bendjennat et al 2003). Another study suggested that the down-regulation of p21 in response to UV irradiation is facilitated by the ubiquitin ligase activity of the Cul4-RING ubiquitin ligase and its substrate recognition subunit DDB2 (CRL4 Ddb2 ) on p53 (Stoyanova et al 2008). Thus, the involvement of the ubiquitin system, in general, and Skp2 or other ubiquitin ligases in particular, in degrading p21 in UV-irradiated cells remains to be clarified.…”
supporting
confidence: 80%
“…These results are consistent with the finding that an ATR-dependent pathway is essential for triggering the down-regulation of p21 after UV irradiation in mammalian cells (Bendjennat et al 2003). Another study suggested that the down-regulation of p21 in response to UV irradiation is facilitated by the ubiquitin ligase activity of the Cul4-RING ubiquitin ligase and its substrate recognition subunit DDB2 (CRL4 Ddb2 ) on p53 (Stoyanova et al 2008). Thus, the involvement of the ubiquitin system, in general, and Skp2 or other ubiquitin ligases in particular, in degrading p21 in UV-irradiated cells remains to be clarified.…”
supporting
confidence: 80%
“…CRL4 DDB2 ubiquitylates histones (23,24) and XPC (25,26) in the nucleotide excision repair (NER) pathway after UV damage. CRL4 DDB2 also ubiquitylates p21 and targets it for ubiquitin-mediated protea-somal degradation (27), and it also ubiquitylates DDB2 itself (28,29).…”
mentioning
confidence: 99%
“…for 26S proteasomal degradation (1,29), and SCF Skp2 and Mdm2, which target p21 for 20S proteasomal degradation (13,18,32). Thus, whether p21 is directly regulated by Pirh2 is worth further investigation.…”
Section: Discussionmentioning
confidence: 99%